Performance Of Cellulose Palm Fiber As An Additive In Asphalt Blends - Jafariahangari, Hossein (2008)

(untitled)
Due to the high oil prices, the cost of asphalt binder has increased tremendously. This scenario has warranted demand for higher viscosity and less expensive asphalt for pavement construction. A study was conducted to take advantage of the empty fruit bunch (EFB) of date and oil palm trees (which are considered as wastes) to produce cellulose fiber to be used as additives in the asphalt binder. If these EFBs could be beneficially utilized in any application, it would reduce the load on the nation’s landfills. This study comprises three stages. At the first stage of the study the EFBs went through chemical and mechanical pulping to produce cellulose fibers, to be used for blending with asphalt binder. The date palm EFB chemical composition revealed alpha cellulose content of 36.1%, which is a very good source of cellulose. At the second stage a total of 11 blends of bio-mastic asphalt (BMA) were prepared. They consisted of 5 blends with chemically pulped date palm fibers, 5 blends with mechanically pulped oil palm fibers and one control sample that contained no fiber. At the third stage of the study, the rheological properties of the bio-mastic asphalt blends were evaluated with the Dynamic Shear Rheometer (DSR) equipment in accordance with the SUPERPAVE Strategic Highway Research Program (SHRP) requirements. The neat asphalt binders (unaged), Rolling Thin Film Oven (RTFO) aged and Pressure Ageing Vessel (PAV) samples were then measured for complex shear modulus, phase angle, shear strain and viscosity with the Dynamic Shear Rheometer (DSR) equipment and then evaluated with the SHRP requirements. The results indicated that the fibers obtained from the date palm EFB showed the best performance and all BMA blends performed very well compared to the control sample. The control sample which was categorized as PG58 was enhanced to PG76 with an addition of 0.375% date palm fiber. The oil palm has also improved the asphalt binder rheological properties from PG58 up to PG70 with the addition of 0.3% oil palm fiber.